2021
DOI: 10.1002/adma.202008267
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stretchable Capacitive Sensors with Different Microstructures

Abstract: Recently, sensors that can imitate human skin have received extensive attention. Capacitive sensors have a simple structure, low loss, no temperature drift, and other excellent properties, and can be applied in the fields of robotics, human-machine interactions, medical care, and health monitoring. Polymer matrices are commonly employed in flexible capacitive sensors because of their high flexibility. However, their volume is almost unchanged when pressure is applied, and they are inherently viscoelastic. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
186
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(188 citation statements)
references
References 234 publications
(473 reference statements)
1
186
0
1
Order By: Relevance
“…Among the various types of pressure sensors, piezoresistive sensors, which can directly convert the applied pressure into an electrical signal, have attracted tremendous attention because of their simple structure, feasible fabrication, high sensitivity, ability to detect both static and dynamic deformation, and ease of system integration and signal acquisition. [ 20–24 ] It has been demonstrated that the change in contact areas/points of conductive sensing materials under applied pressure significantly determines the electrical properties of the pressure sensing materials. Therefore, in recent years, much effort has been devoted to constructing materials into delicate microstructures with low modulus, enabling them to respond sensitively to subtle pressure stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of pressure sensors, piezoresistive sensors, which can directly convert the applied pressure into an electrical signal, have attracted tremendous attention because of their simple structure, feasible fabrication, high sensitivity, ability to detect both static and dynamic deformation, and ease of system integration and signal acquisition. [ 20–24 ] It has been demonstrated that the change in contact areas/points of conductive sensing materials under applied pressure significantly determines the electrical properties of the pressure sensing materials. Therefore, in recent years, much effort has been devoted to constructing materials into delicate microstructures with low modulus, enabling them to respond sensitively to subtle pressure stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sensors can convert external activity (such as mechanical deformation) into directly measurable electrical signals. Depending on their sensory mechanism, they can be divided into resistive [ 27 ], piezoelectric [ 28 ], capacitive [ 29 ], and other types of friction [ 30 ]. When the external pressure changes, the appropriate resistance value, capacitance value, or voltage value of the flexible sensor changes accordingly.…”
Section: Sensory Mechanisms Of Flexible Sensorsmentioning
confidence: 99%
“…These complex manufacturing processes cause low yields and high costs. In [21], flexible capacitive strain sensors with different microstructures were developed. The different strain microstructures exhibited issues related to stretchability, a complicated manufacturing process, low yields, and high costs.…”
Section: Introductionmentioning
confidence: 99%